Mind how you cross the gap! Outcomes for young people who failed to make the transition from child to adult services: the TRACK study - Islam,Z; Ford,T; Kramer,T; Paul,M; Parsons,H; Harley,K; Weaver,T; McLaren,S; Singh,SP (BJPsych Bulletin, 2016)
Aims and method The Transitions of Care from Child and Adolescent Mental Health Services to Adult Mental Health Services (TRACK) study was a multistage, multicentre study of adolescents' transitions between child and adult mental health services undertaken in England. We conducted a secondary analysis of the TRACK study data to investigate healthcare provision for young people (n = 64) with ongoing mental health needs, who were not transferred from child and adolescent mental health services (CAMHS) to adult mental health services mental health services (AMHS). Results The most common outcomes were discharge to a general practitioner (GP; n = 29) and ongoing care with CAMHS (n = 13), with little indication of use of third-sector organisations. Most of these young people had emotional/neurotic disorders (n = 31, 48.4%) and neurodevelopmental disorders (n = 15, 23.4%). Clinical implications GPs and CAMHS are left with the responsibility for the continuing care of young people for whom no adult mental health service could be identified. GPs may not be able to offer the skilled ongoing care that these young people need. Equally, the inability to move them decreases the capacity of CAMHS to respond to new referrals and may leave some young people with only minimal support.